The case of the cryptic crinoline : an Enola Holmes mystery / 5 - Springer, Nancy (An Enola Holmes Mystery, 2009)
In late nineteenth-century London, fourteen-year-old Enola Holmes, much younger sister of detective Sherlock Holmes, turns to Florence Nightingale for help when her investigation into the disappearance of a Crimean War widow grows cold.